The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1371/journal.pone.0201344
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of recommended approaches for containment and safe handling of human excreta in emergency settings

Abstract: Ebola and cholera treatment centres (ETC and CTC) generate considerable quantities of excreta that can further the transmission of disease amongst patients and health workers. Therefore, approaches for the safe handling, containment and removal of excreta within such settings are needed to minimise the likelihood of onward disease transmission. This study compared the performance and suitability of three chlorine-based approaches (0.5% HTH, NaDCC and NaOCl (domestic bleach)) and three lime-based approaches (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…Results of a previous research project undertaken at the University of Brighton (Applied Research on Disinfection to Prevent Ebola Transmission and funded by USAID) assessed the efficacy of various 0.5% (5000 mg/L) chlorine solutions (HTH, NaDCC, and household bleach) and hydrated lime suspensions (10%, 20%, and 30% (w:v)) at removing viruses and bacteria within excreta matrices. These recently published results [34] demonstrated that lime suspensions, particularly at 30% w/v, were considerably more effective than 0.5% chlorine solutions, especially when excreta matrices contained high concentrations of solids and organic matter. However, a chlorine solution of only 0.5% [9][10][11] was used for this previous study, which is considerably lower than the MSF cholera guideline [12], which recommends the use of 2% (20,000 mg/L) chlorine solutions for the containment and disinfection of human excreta in CTCs.…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…Results of a previous research project undertaken at the University of Brighton (Applied Research on Disinfection to Prevent Ebola Transmission and funded by USAID) assessed the efficacy of various 0.5% (5000 mg/L) chlorine solutions (HTH, NaDCC, and household bleach) and hydrated lime suspensions (10%, 20%, and 30% (w:v)) at removing viruses and bacteria within excreta matrices. These recently published results [34] demonstrated that lime suspensions, particularly at 30% w/v, were considerably more effective than 0.5% chlorine solutions, especially when excreta matrices contained high concentrations of solids and organic matter. However, a chlorine solution of only 0.5% [9][10][11] was used for this previous study, which is considerably lower than the MSF cholera guideline [12], which recommends the use of 2% (20,000 mg/L) chlorine solutions for the containment and disinfection of human excreta in CTCs.…”
Section: Introductionmentioning
confidence: 82%
“…It is interesting to note that the 30% lime solution did not lose its efficacy even as the load of organic matter and suspended solids increased in the excreta matrices from 0% to 10% and 20%. As mentioned previously, this study evolved from (and built upon findings of) earlier research [34]. However, the study differed (as outlined in the materials and methods section) in that it focused on trying to understand the performance of higher chlorine concentrations (1% and 2%), and different volumes (125 mL) of the chlorine solutions and lime suspension to treat and contain human excreta.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations